2020
DOI: 10.31234/osf.io/3ezmw
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Are There Reliable Qualitative Individual Difference in Cognition?

Abstract: In this paper we propose a new set of questions that focus on the direction of effects. In almost all studies the direction is important. For example, in a Stroop task it implies one theoretical explanation if incongruent words are slowed relative to congruent ones, but a completely different theoretical explanation if congruent words are slowed down relative to incongruent ones. We ask a 'does everybody' question, such as, 'does every individual show a Stroop effect?' Or, 'does every individual respond faster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(40 citation statements)
references
References 20 publications
1
39
0
Order By: Relevance
“…The number of observations per person is particularly important because without this, the posterior inclusion probabilities tend to cluster around 0.5, giving no preference to whether an individual is "average" or not. The exact number of trials per person will depend on the ratio of between-person to residual variance, but it has been suggested that a minimum of 100 trials per person per condition may be needed (Rouder & Haaf, 2020). Researchers should bear this cost in mind when considering individual differences research.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The number of observations per person is particularly important because without this, the posterior inclusion probabilities tend to cluster around 0.5, giving no preference to whether an individual is "average" or not. The exact number of trials per person will depend on the ratio of between-person to residual variance, but it has been suggested that a minimum of 100 trials per person per condition may be needed (Rouder & Haaf, 2020). Researchers should bear this cost in mind when considering individual differences research.…”
Section: Discussionmentioning
confidence: 99%
“…The main advantages of our proposed methodology are that it allows the quantification of evidence for or against individual random effects, and because it can be fit using standard statistical software, it is flexible enough to be applied to a broad class of models (i.e., generalized linear mixed models). We seek to address a set of questions inspired by those in Grice et al (2020) and Rouder and Haaf (2020), but differ in an important way. With this framework we explicitly address the individual by providing a tool that is capable of answering which individuals are "average" and which ones are not?…”
Section: Major Contributionmentioning
confidence: 99%
See 2 more Smart Citations
“…We find that researchers often stake out positions about individual differences a priori, and believe them with a surprising degree of confidence. One position we encounter is what we call the arbitrary diversity hypothesis (Rouder & Haaf, 2020). Accordingly, the human condition is so diverse that there must be people who deviate in all behaviors.…”
mentioning
confidence: 99%